2014
DOI: 10.1007/s00221-014-3997-7
|View full text |Cite
|
Sign up to set email alerts
|

Conditioned pain modulation in temporomandibular disorders (TMD) pain patients

Abstract: The aims were to investigate (1) if temporomandibular disorders (TMD) patients with temporomandibular joint (TMJ) pain had different conditioned pain modulation (CPM) compared with healthy subjects and, (2) if clinical pain characteristics influenced CPM. Sixteen TMD pain patients and 16 age-matched healthy subjects were participated. A mechanical conditioning stimulus (CS) was applied to pericranial muscles provoking a pain intensity of 5/10 on a visual analogue scale. Pressure pain thresholds (PPT) and press… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
60
2
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 68 publications
(72 citation statements)
references
References 29 publications
3
60
2
3
Order By: Relevance
“…King et al 37 reported less efficient CPM in these patients; Garrett et al 24 reported CPM similar to healthy controls, whereas Kothari et al 42 reported reduced CPM in TMDs after surgery. Oono et al 69 reported reduced CPM in TMD, but only when measured from affected sites. For other disorders, a report on interstitial cystitis found reduced CPM, 60 whereas 2 reports on vestibulodynia found normal CPM.…”
Section: Idiopathic Pain Syndromesmentioning
confidence: 97%
“…King et al 37 reported less efficient CPM in these patients; Garrett et al 24 reported CPM similar to healthy controls, whereas Kothari et al 42 reported reduced CPM in TMDs after surgery. Oono et al 69 reported reduced CPM in TMD, but only when measured from affected sites. For other disorders, a report on interstitial cystitis found reduced CPM, 60 whereas 2 reports on vestibulodynia found normal CPM.…”
Section: Idiopathic Pain Syndromesmentioning
confidence: 97%
“…63,64 The CPM response was predicted by clinical peak pain intensity, again indicating that ongoing pain affects the balance between inhibitory and excitatory pathways or that the balance between inhibitory and excitatory pathways affects clinical peak pain intensity. The relationship between clinical pain intensity and the CPM response has previously been studied in patients with neuropathy 29,30 and temporomandibular disorder, 65 with 2 studies finding an inverse relationship 29,30 and 1 study reporting no relationship. 65 EIH Impaired EIH has previously been shown in chronic pain conditions such as chronic widespread pain, 12 chronic whiplash-associated disorder.…”
Section: Cpmmentioning
confidence: 98%
“…The relationship between clinical pain intensity and the CPM response has previously been studied in patients with neuropathy 29,30 and temporomandibular disorder, 65 with 2 studies finding an inverse relationship 29,30 and 1 study reporting no relationship. 65 EIH Impaired EIH has previously been shown in chronic pain conditions such as chronic widespread pain, 12 chronic whiplash-associated disorder. 26 The present study extends these findings by showing reduced hypoalgesia after aerobic and isometric exercises and increased TS of pain after aerobic exercise in patients with high pain sensitivity compared with patients with low pain sensitivity.…”
Section: Cpmmentioning
confidence: 98%
“…It is structured based on a well-known, validated tool for the evaluation of the subjective perception of pain intensity (Ferreira-Valente et al, 2011;Oono et al, 2014). The Orgasmometer (Data S1) ranges from 0 to 10, where 0 corresponds with the absence of orgasmic intensity and 10 with the highest level of orgasmic intensity.…”
Section: The Orgasmometermentioning
confidence: 99%